Distinct mechanisms shape soil bacterial and fungal co-occurrence networks in a mountain ecosystem. Issue 4 (28th February 2020) - Li, Jiabao; Li, Chaonan; Kou, Yongping; Yao, Minjie; He, Zhili; Li, Xiangzhen
ABSTRACT: Understanding microbial network assembly is a promising way to predict potential impacts of environmental changes on ecosystem functions. Yet, soil microbial network assembly in mountain ecosystems and its underlying mechanisms remain elusive. Here, we characterized soil microbial co-occurrence networks across 12 altitudinal sites in Mountain Gongga. Despite differences in habitats, soil bacterial networks separated into two different clusters by altitude, namely the lower and higher altitudes, while fungi did not show such a pattern. Bacterial networks encompassed more complex and closer relationships at the lower altitudes, while fungi had closer relationships at the higher altitudes, which could be attributed to niche differentiation caused by high variations in soil environments and plant communities. Both abiotic and biotic factors (e.g. soil pH and bacterial community composition) shaped bacterial networks. However, biotic factors played more important roles than the measured abiotic factors for fungal network assembly. Further analyses suggest that multiple mechanisms including niche overlap/differentiation, cross-feeding and competition between microorganisms could play important roles in shaping soil microbial networks. This study reveals microbial co-occurrence networks in response to different ecological factors, which provides important insights into our comprehensive understanding of microbial network assembly and their functional potentials in mountain ecosystems. Abstract : Soil bacterial and fungal co-occurrence networks in a hotspot mountain ecosystem are shaped by both biotic and abiotic factors.